Restructuring the network of public science and technology organizations - Bach, Dinh Viet (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2018)
The network of public science and technology (S&T) organizations of Vietnam is very big in quantity. However, the structure of the network, organizational and operational mechanism remains to have problems to recover. Therefore, the network of public S&T organizations needs to be restructured in direction of maximal reduction of the number of these organizations. Three measures are to be applied: mergence to universities, mergence to enterprises and dissolution. Only those public S&T organizations which operate in priority and key important sectors or which other economic non-public sectors do not want, have no investment capacity or are not allowed to make investment for can be retained. Code: 17122501